The Effect of New Rural Cooperative Medical Scheme on the Socioeconomic Inequality in Inpatient Service Utilization Among the Elderly in China - Sun J; Lyu X; Yang F (Dove Medical Press, 2020)
Jian Sun,1 Xiaoyin Lyu,2 Fan Yang1,3 1School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai 200030, People’s Republic of China; 2High School Affiliated to Shanghai Jiao Tong University, Shanghai 200439, People’s Republic of China; 3China Institute for Urban Governance, Shanghai Jiao Tong University, Shanghai 200030, People’s Republic of ChinaCorrespondence: Fan YangSchool of International and Public Affairs, Shanghai Jiao Tong University, Shanghai 200030, People’s Republic of ChinaTel +86-137-7430-5290Email fan_yang86@sjtu.edu.cnBackground and Aim: Health equity is an important goal of health policy, and the equalization of access to health care plays a vital role in guaranteeing it. The aim of this study was to use the cross-sectional data to explore the effect of New Rural Cooperative Medical Scheme (NRCMS) on the socioeconomic inequality in inpatient service utilization among the elderly in china.Methods: The data of this study were obtained from the 2018 wave of China Family Panel Studies (CFPS), involving 3645 older adults aged 60 and above. Furthermore, concentration index and concentration curve were employed to measure the socioeconomic inequality in inpatient service utilization. Moreover, this study used multiple linear regression model to explore the effect of NRCMS on inpatient service utilization. In addition, this study adopted the decomposition of concentration index to investigate the effect of NRCMS on the socioeconomic inequality of inpatient service utilization.Results: The concentration index of inpatient expense for the older people was 0.0538, and its concentration curve lays below the diagonal. The regression result indicates that NRCMS was significantly associated with higher inpatient expense among the elderly (coefficient = 0.8749, p < 0.01). The decomposition result reveals that the contribution rate of NRCMS to concentration index was − 2.29%, which indicates that its contribution on reducing pro-rich inequality in inpatient service utilization was limited.Conclusion: This study demonstrates that there was a pro-rich inequality in inpatient service utilization among the elderly. Furthermore, NRCMS was significantly associated with higher inpatient expense. Moreover, NRCMS only played a limited role in reducing pro-rich inequality in inpatient service utilization.Keywords: socioeconomic inequality, inpatient service utilization, elderly, New Rural Cooperative Medical Scheme, China